ANALISIS PEMASARAN UMKM GULA AREN DI DESA BOLOBUNGKANG KECAMATAN NUHON KABUPATEN BANGGAI - Pakaji, Fajri; Djamaluddin, Ismail; Puspapratiwi, Dian; Enteding, Trianto (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
Palm sugar is an important commodity for the economy in rural areas. One of the things that is an obstacle for palm sugar farmers is the marketing information of palm sugar that affects farmers' income. The purpose of this study is to find out the marketing channels of Micro, Small and Medium Enterprises (MSMEs) Palm Sugar in Bolobungkang Village, Nuhon District Banggai Regency. This research was carried out from April to July 2023. The research site was carried out in Bolobungkang Village, Nuhon District, Banggai Regency. Determining the population and sample in the research that will be carried out is 30 sugar palm farmers who are also palm sugar entrepreneurs, 9 retail traders, 3 people who are collectors.The research results show that there are two marketing channels for palm sugar from farmers to consumers. The marketing margin for collecting traders is IDR. 1,500/piece and at wholesalers Rp. 1,500/piece. Marketing costs for collecting traders are IDR. 179.30/piece and wholesalers Rp. 657.48/piece. The profit obtained by collecting traders is IDR. 1320.70/piece and for wholesalers Rp. 825.52/piece.